Characteristics of carbohydrate counting practice associated with adequacy of glycated hemoglobin in adults with type 1 diabetes mellitus in Brazil - Uliana, Gabriela Correia; Camara, Lediane Nunes; Paracampo, Carla Cristina Paiva; da Costa, Juliana Carvalho; Gomes, Daniela Lopes (Frontiers in Endocrinology, 2023)
Background The Carbohydrate Counting (CC) is directly associated with achieving glycemic control by people with Type 1 Diabetes Mellitus (T1DM). Therefore, this study aims to analyze characteristics of the CC practice associated with the adequacy of glycated hemoglobin (HbA1c) in adults with T1DM in Brazil. Methods The study was cross-sectional, carried out using an online form with questions about knowledge of CC, clinical, anthropometric, sociodemographic data, follow-up with health professionals and understanding of the concepts of CC. Pearson’s chi-square test and binomial logistic regression analysis (p<0.05) were applied. Results 173 adults participated, of which 57.2% had increased HbA1c (≥7%). Having the diabetes duration <10 years (p=0.006), performing the CC at lunch (p=0.040) and dinner (p=0.018), using specific applications to perform the CC (p=0.001), having learned to perform CC with a nutritionist (p=0.037) and knowing how to correctly define the concepts of food bolus (p=0.001), correction bolus (p<0.001) and insulin/carbohydrate ratio (p<0.001) was associated with having adequate HbA1c (<7%). Participants who were undergoing CC practice were 3.273 times more likely to have adequate HbA1c and participants with diabetes duration <10 years were 2.686 times more likely to have adequate HbA1c. Conclusion It was concluded that variables transversal to CC favor adequate HbA1c values in adults with T1DM and that practicing CC and having a diabetes duration of less than 10 years are predictive factors of having adequate HbA1c.